Personality and cross-cultural adjustment among expatriate assignees in Malaysia - Sri Ramalu, Subramaniam; Che Rose, Raduan; Uli, Jegak; Samy, Naresh Kumar (Canadian Center of Science and Education, 2010)
This paper investigates the affects of Big Five personality and its dimensions on expatriate cross-cultural adjustment. Based on sample of 332 expatriates working in Malaysia, personality factor found to be a significant determinant of expatriate cross-cultural adjustment in international assignments. Specifically, the results of this study reveal that expatriates in Malaysia with greater agreeableness personality fared better in their general and interaction adjustment. Those with greater extraversion found to adjust better in general environment. Those with greater conscientiousness and openness to experience adjusted better to the work environment. The findings of this study contributes to the body of knowledge in the cross-cultural management field and have practical implication to expatriating firms especially in the area of selection and training of candidates for international assignments.